Do the dispersion properties of electromagnetic surface waves at the sharp boundary plasma-metal in slab Voigt geometry represent the limiting case of those for the interface of two plasmas? - Girka, I.O.; Thumm, M. (Problems of Atomic Science and Technology, 2023)
Electromagnetic surface waves in Voigt geometry are considered to resolve the contradiction between two clas-sical studies. One investigated the waves at the boundary of two plasmas. These waves were reported not to propa-gate with frequencies below the ion cyclotron frequency. The other approach studied the waves at the metal-plasma interface. Dispersion properties of the waves with frequencies below the ion cyclotron frequency were investigated. Розглянуто електромагнітні поверхневі хвилі в геометрії Фойгта з метою усунути протиріччя між двома класичними дослідженнями. Одне досліджувало хвилі на межі двох плазмових середовищ, і було показано, що хвилі не поширюються на частотах нижче іонної циклотронної. Інше – вивчало хвилі на межі метал-плазма, і було досліджено дисперсійні властивості хвиль, нижче іонної циклотронної частоти.